Pathogenicity and resistance to antifungals-fungicides in Fusarium and Neocosmospora A One health approach (2024)
The primary objective of this doctoral thesis was to determine the presence of Fusarium and Neocosmospora in humans, animals, and plants through a One Health approach. To achieve this, we conducted phenotypic and molecular studies on samples obtained from various environments and human strains in Colombia to identify Fusarium or Neocosmospora. Our research revealed that Neocosmospora keratoplastica and Neocosmospora falciformis are prevalent in samples collected from humans, animals, and the environment (soil and sand). Notably, we describe Sea Turtle Egg Fusariosis (STEF) in sea turtles in Colombia for the first time. Furthermore, to find differences in how Fusarium/Neocosmospora interacts with hosts, we employed a Galleria mellonella animal model. We inoculated the larvae with clinical, animal, and environmental samples to carry out this experiment. We observed similar effects on mortality when the larvae were exposed to 1.5x106 UCF / ml of inoculum and incubated in a maintained incubation at 25 ° C. Also, it was observed that human, animal, and environmental samples can induce mortality in larvae at 37°C. Moreover, we determined the in vitro susceptibility profile of 52 isolates towards antifungal and fungicides. Our findings confirmed high Minimum Inhibitory Concentrations (MICs) to itraconazole, posaconazole, propiconazole, tebuconazole, and difenoconazole. However, amphotericin B and voriconazole showed susceptibility in most of the isolates. Subsequently, we aimed to investigate the antifungal effectiveness of molecules involved in Protein Kinase signaling pathways against Fusarium/Neocosmospora clinical isolates (n=12). To do this, we performed an in vitro test using four different inhibitors: the Pkc1 inhibitor (NPC15437), the p38 MAPK inhibitor (SKF 86002), the human Hsp90-Cdc37 inhibitor (Celastrol), and the antiparasitic drug Miltefosine. Our results indicate that the PKC1 inhibitor (NPC15437) and Miltefosine have promising antifungal activity. Finally, we address the challenges of diagnosing fungal keratitis in clinical and microbiologic settings. This was achieved through a survey of healthcare workers and collaboration with ophthalmologists, clinical microbiologists, and biodesigners to perform the design drafts and initial sketches of a medical device for corneal scraping.